Both/and thinking : embracing creative tensions to solve your toughest problems - Smith, Wendy K.; Lewis, Marianne W. (Boston, Massachusetts : Harvard Business Review Press, 2022)
"Life is full of paradoxes. How can we each express our individuality and be a team player? How do we balance work and life? How can we take care of ourselves while supporting others? How can we manage the core business while innovating for the future? For many of us, these competing and interwoven demands are a source of conflict. Since our brains love to make either-or choices, we choose one option over the other. We deal with the uncertainty by asserting certainty. There's a better way. In Both/And Thinking, Wendy Smith and Marianne Lewis help readers cope and thrive with multiple, knotted tensions at the same time. Drawing from more than twenty years of pioneering research, they provide an actionable framework for transforming these tensions into opportunities for innovation and personal growth. Filled with practical advice, groundbreaking research, and fascinating stories, Both/And Thinking will completely change the way you approach your most vexing problems"--
Foreword : The power of both/and thinking in a vexing world / Amy C. Edmondson -- Introduction: Why some problems are so challenging -- Part One: Foundations : the promise and perils of paradox. Experiencing tensions : Why paradox? Why now? -- Getting caught in vicious cycles : rabbit holes, wrecking balls, and trench warfare -- Part Two: Approaches : the paradox system. Enabling virtuous cycles with the paradox system : mules and tightrope walkers -- Shifting to both/and assumptions : towards a paradox mindset -- Creating boundaries to contain tensions : structures to stabilize uncertainty -- Finding comfort in discomfort : emotions that accommodate tensions -- Enabling dynamics that unleash tensions: Changes that avoid the ruts -- Part Three: Applications : both/and thinking in practice. Individual decisions : Should I stay or should I go? -- Interpersonal relationships : mending a widening divide -- Organizational leadership : enabling sustainable impact -- Appendix: Paradox mindset inventory.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (ProQuest Ebook Central, viewed April 11, 2023).
WorldCat record variable field(s) change: 050
Keywords: Multiple criteria decision making; Creative ability in business; Choice (Psychology); Problem solving; Success in business; Choice Behavior; Problem Solving; Décision multicritère; Créativité dans les affaires; Choix (Psychologie); Résolution de problème; Succès dans les affaires; Choice (Psychology); Creative ability in business; Multiple criteria decision making; Problem solving; Success in business